Multi-objective optimization of nitinol stent design. (September 2017) - Alaimo, G.; Auricchio, F.; Conti, M.; Zingales, M.
Highlights: An enhanced nitinol stent design, characterized by the use of a tapered profile strut, is introduced. The advantages of the tapered strut profile, in term of fatigue life enhancement and stent scaffolding capabilities, are shown. Cell design with tapered struts has been optimized through a multi-objective shape optimization coupled with finite element analysis. A marked improvement of the fatigue safety factor, i.e. about 2.4 times, compared to the typical design, is achieved without any loss of scaffolding capabilities. Abstract: Nitinol stents continuously experience loadings due to pulsatile pressure, thus a given stent design should possess an adequate fatigue strength and, at the same time, it should guarantee a sufficient vessel scaffolding. The present study proposes an optimization framework aiming at increasing the fatigue life reducing the maximum strut strain along the structure through a local modification of the strut profile.The adopted computational framework relies on nonlinear structural finite element analysis combined with a Multi Objective Genetic Algorithm, based on Kriging response surfaces. In particular, such an approach is used to investigate the design optimization of planar stent cell.The results of the strut profile optimization confirm the key role of a tapered strut design to enhance the stent fatigue strength, suggesting that it is possible to achieve a marked improvement of both the fatigue safety factor and the scaffolding capability simultaneously. The present study underlines the value of advanced engineering tools to optimize the design of medical devices.